Analisis Pengaruh Return On Asset (ROA), Likuiditas, dan Solvabilitas Terhadap Price to Book Value (PBV) pada Perusahaan Tekstil dan Garmen yang Go Public di Bursa Efek Indonesia Periode 2008-2013 - Nurviana, Devi, Drs. Syamsudin, M.M (2016)
Price to book value is a rate used to compare company whether the company relatively higher or cheaper if compared to other share.The high price to book value says that the good prospect company.Company will be more good at creating value to the shareholders.Big or small the price to book value influenced by several factors, good factors and non-financial.This study aims to to test the influence of return on assets liquidity, and the solvability of to price to book value. A population that used in the this is a company textile and garment listed on the efek indonesia the period 2008-2013 .A method of the sample collection by means of purposive sampling in accordance with the criteria which had been determined , so the total sample obtained as much as 13 .While the total the data used in research as many as 78 .The method of analysis data using the hypothesis from the analysis linear regression multiple , test normality , and the assumption classical. The research results show that the variable liquidity and solvability have had a positive impact on price to book value .This shows that the variable liquidity and the solvability of higher will increase price to book value , but the low variable liquidity and solvability to lower price to book value to companies textile and garment .While for variables return on assets has not been affecting the price to book value .This shows the amount return on assets will not affect high the low price to book value.